Voids in the Cosmic Web as a probe of dark energy - Novosyadlyj, B.; Tsizh, M. (Condensed Matter Physics, 2017)
The formation of large voids in the Cosmic Web from the initial adiabatic cosmological perturbations of spacetime metric, density and velocity of matter is investigated in cosmological model with the dynamical dark energy accelerating expansion of the Universe. It is shown that the negative density perturbations with the initial radius of about 50 Mpc in comoving to the cosmological background coordinates and the amplitude corresponding to the r.m.s. temperature fluctuations of the cosmic microwave background lead to the formation of voids with the density contrast up to −0.9, maximal peculiar velocity about 400 km/s and the radius close to the initial one. An important feature of voids formation from the analyzed initial amplitudes and profiles is establishing the surrounding overdensity shell. We have shown that the ratio of the peculiar velocity in units of the Hubble flow to the density contrast in the central part of a void does not depend or weakly depends on the distance from the center of the void. It is also shown that this ratio is sensitive to the values of dark energy parameters and can be used to find them based on the observational data on mass density and peculiar velocities of galaxies in the voids. В роботi дослiджено формування великих порожнин з початкових космологiчних адiабатичних збурень метрики простору-часу та густини i швидкостi матерiї в моделях Всесвiту з динамiчною темною енергiєю, що зумовлює прискорене розширення Всесвiту. Показано, що вiд’ємнi збурення густини з початковим розмiром близько 50 Mpc в супутнiх до космологiчного фону координатах та амплiтудою, що вiдповiдає спостережуваним середньоквадратичним флуктуацiям температури мiкрохвильового релiктового випромiнювання, приводять до утворення порожнин з контрастом густини матерiї аж до −0.9, максимумом пекулярної швидкостi близько 400 км/c та з радiусом близьким до початкового. Важливою особливiстю дослiджених початкових профiлiв густини є формування оточуючої оболонки згущення. Показано, що вiдношення пекулярної швидкостi в одиницях габблiвського потоку до контрасту густини в центральнiй частинi порожнини не залежить або слабо залежить вiд вiдстанi вiд центра порожнини. Показано, що таке спiввiдношення є чутливим до значень параметрiв темної енергiї i може бути використане для їх знаходження на основi даних про структуру порожнин та пекулярнi швидкостi галактик у них